2010
DOI: 10.1182/blood.v116.21.3879.3879
|View full text |Cite
|
Sign up to set email alerts
|

Early Interim 18f-FDG PET In Hodgkin's Lymphoma: Evaluation on 304 Patients

Abstract: 3879 Purpose. The use of early (interim) positron emission tomography (PET) restaging during front-line therapy in Hodgkin's lymphoma (HL) has considerably increased in clinical practice as an early recognition of treatment failure allows patients to be addressed to more intensive treatment regimens. Patients and Methods. Between June 1997 and June 2009, 304 newly-diagnosed Hodgkin's lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…Notably, even end‐PET positive patients fared well with a 4‐year OS of 84%, re‐emphasizing the efficacy of available salvage therapies for relapsed low‐risk patients. These results contrast with that recently reported by Zinzani the prognostic role of interim PET in a large retrospective cohort of 304 HL patients, half of them (147) with early‐stage disease. Patients were treated with ABVD × 4 + IFRT or ABVD × 6 without RT in two Italian Institutions: 128 (87%) had a negative and 19 (13%) a positive PET‐2: the 9‐y PFS was 94.7% and 31.3%, respectively ( P = 0.0000).…”
Section: Discussionmentioning
confidence: 96%
“…Notably, even end‐PET positive patients fared well with a 4‐year OS of 84%, re‐emphasizing the efficacy of available salvage therapies for relapsed low‐risk patients. These results contrast with that recently reported by Zinzani the prognostic role of interim PET in a large retrospective cohort of 304 HL patients, half of them (147) with early‐stage disease. Patients were treated with ABVD × 4 + IFRT or ABVD × 6 without RT in two Italian Institutions: 128 (87%) had a negative and 19 (13%) a positive PET‐2: the 9‐y PFS was 94.7% and 31.3%, respectively ( P = 0.0000).…”
Section: Discussionmentioning
confidence: 96%
“…Overall, the methodological quality of included studies was moderate. There was moderate risk of bias for the domain of prognostic factor measurement in six studies, because five studies (Gallamini et al, 2007;Cerci et al, 2010;Straus et al, 2011;Markova et al, 2012;Zinzani et al, 2012) used a stand-alone PET system rather than integrated PET/CT, and one study did not report at all which PET system was used (Furth et al, 2011). In addition, there was moderate risk of bias for the domain of outcome measurement in five studies, because four studies (Gallamini et al, 2007;Markova et al, 2012;Filippi et al, 2013;Rossi et al, 2014) did not report the reference criteria for the confirmation of treatment failure and one study reported that histology was not used to confirm treatment failure in all cases (Straus et al, 2011).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Therefore, Gallamini et al's results [3,4] have been seriously biased. In other studies on the value of interim FDG-PET/CT in patients with advanced-stage Hodgkin lymphoma treated with ABVD, the predictive value was less strong, with PFS rates ranging between 28.8% and 43% for those with positive interim FDG-PET/CT results [6][7][8]. Of note, in two recent studies including an ABVD treated cohort of early-and advanced-stage Hodgkin lymphoma patients, interim FDG-PET/CT had minor or no predictive value at all, with interim FDG-PET/CT positive patients having PFS of 56.3% [9] and 100% [10], respectively.…”
Section: Fundingmentioning
confidence: 95%